Grammatical Structures and Relational Dynamics in Sundanese: An SFL Perspective - Kelik Wachyudi; Wawan Gunawan; Dadang Sudana; Iwa Lukmana (Aksara, 2024)
This study aims to describe and identify various types of relational processes found in Sundanese. The analysis is conducted using the perspective of Functional Systemic Linguistics, with a special focus on the transitivity system in the Sundanese language structure. The research method used is a qualitative descriptive approach. The data collection technique in this research is sourced from Mangle magazine. The data analysis technique involves classifying the clauses into attributive and identifying relational processes based on the transitivity system in Functional Systemic Linguistics. The results show that the texts in the Sundanese-language Mangle magazine contain typical Sundanese relational processes. The types of relational processes found are attributive and identifying relational processes. Each of these types is further divided into more specific categories: intensive, possessive, and circumstantial. AbstrakPenelitian ini bertujuan untuk mendeskripsikan dan mengidentifikasi berbagai jenis proses relasional yang terdapat dalam bahasa Sunda. Analisis dilakukan dengan menggunakan perspektif Linguistik Sistemik Fungsional, dengan fokus khusus pada sistem transitivitas dalam struktur bahasa Sunda. Adapun metode penelitian yang digunakan adalah pendekatan deskriptif kualitatif.  Teknik pengumpulan data dalam penelitian ini bersumber majalah Mangle. Teknik analisis data dalam penelitian ini dilakukan dengan mengklasifikasikan klausa-klausa ke dalam proses relasional atributif dan identifikatif berdasarkan perspektif sistem transitivitas dalam Linguistik Sistemik Fungsional. Hasil penelitian menunjukkan bahwa teks-teks dalam majalah Mangle berbahasa Sunda mengandung proses relasional khas bahasa Sunda. Jenis proses relasional yang ditemukan adalah proses relasional atributif dan proses relasional identifikatif. Masing-masing dari kedua jenis proses relasional tersebut selanjutnya terbagi lagi menjadi tipe-tipe yang lebih spesifik, seperti intensive, possessive, dan circumstantial.